Neoadjuvant chemotherapy with gemcitabine plus cisplatin followed by radical liver resection versus immediate radical liver resection alone with or without adjuvant chemotherapy in incidentally detected gallbladder carcinoma after simple cholecystectomy or in front of radical resection of BTC (ICC/ECC) – a phase III study of the German registry of incidental gallbladder carcinoma platform (GR)– the AIO/ CALGP/ ACO- GAIN-trial – - Thorsten O. Goetze; Wolf O. Bechstein; Ulli Simone Bankstahl; Tobias Keck; Alfred Königsrainer; Sven A. Lang; Claudia Pauligk; Pompiliu Piso; Arndt Vogel; Salah-Eddin Al-Batran (BMC Cancer, 2020)
Abstract Background Currently, complete surgical resection represents the only potentially curative treatment option for Biliary Tract Cancer (BTC) including Gallbladder Cancer (GBC). Even after curative resection, 5-year OS is only 20–40%. Gallbladder carcinoma is relatively rare, but still the fifth most common neoplasm of the digestive tract and even the most frequent cancer of the biliary system. Gallbladder carcinoma is suspected preoperatively in only 30% of all pts., while the majority of cases are discovered incidentally by the pathologist after cholecystectomy for a benign indication. For improving curative rates in BTC and GBC, early systemic therapy combined with radical resection seems to be a promising approach. The earliest moment to apply chemotherapy would be in front of radical surgery. The encouraging results of neoadjuvant/perioperative concepts in other malignancies provide an additional rationale to use this treatment in the early phase of GBC management and even ICC/ECC. Especially because data regarding pure adjuvant chemotherapy in BTC’s are conflicting. Methods This is a multicenter, randomized, controlled, open-label phase III study including pts. with incidentally discovered GBCs after simple cholecystectomy in front of radical liver resection and pts. with resectable/ borderline resectable cholangiocarcinomas (ICC/ ECC) scheduled to receive perioperative chemotherapy (Gemcitabine + Cisplatin 3 cycles pre- and post-surgery) or surgery alone followed by a therapy of investigator’s choice. Primary endpoint is OS; secondary endpoints are PFS, R0-resection rate, toxicity, perioperative morbidity, mortality and QoL. A total of N = 333 patients with GBC or BTC will be included. Recruitment has started in August 2019. Discussion The current proposed phase III GAIN study investigates whether induction chemotherapy followed by radical resection in ICC/ECC and re-resection in IGBC (and – if possible – postoperative chemotherapy) prolongs overall survival compared to radical surgery alone for incidental gallbladder carcinoma and primary resectable or borderline resectable cholangiocarcinoma. Utilizing a neoadjuvant approach including a second radical surgery will help to raise awareness for the necessity of radical surgery, especially second radical completion surgery in IGBC and improve the adherence to the guidelines. Trial registration ClinicalTrials.gov ID: NCT03673072 from 17.09.2018. EudraCT number: 2017–004444-38 from 02.11.2017.